2020
DOI: 10.3389/fphys.2020.562824
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Arterial Elastance During Experimental Endotoxic Septic Shock: A Potential Marker of Cardiovascular Efficiency

Abstract: Dynamic arterial elastance (Ea dyn ), the ratio between pulse pressure variation (PPV) and stroke volume variation (SVV), has been suggested as a dynamic parameter relating pressure and flow. We aimed to determine the effects of endotoxic septic shock and hemodynamic resuscitation on Ea dyn in an experimental study in 18 New Zealand rabbits. Animals received placebo (SHAM, n = 6) or intravenous lipopolysaccharide (E. Coli 055:B5, 1 mg⋅kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Nevertheless, the AUC of 0.74 is at the marginal value to be regarded as a good predictor. This potential correlation between Ea and preload responsiveness was likely not by chance, since a recent study has explored the possibility of dynamic arterial elastance as a potential marker of cardiovascular efficiency [32] . Moreover, the previous experimental study suggested that aortic wall edema caused by sepsis could contribute to a persistent elevation in aortic characteristic impedance leading to an impaired arterial load and ventriculoarterial decoupling [33] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, the AUC of 0.74 is at the marginal value to be regarded as a good predictor. This potential correlation between Ea and preload responsiveness was likely not by chance, since a recent study has explored the possibility of dynamic arterial elastance as a potential marker of cardiovascular efficiency [32] . Moreover, the previous experimental study suggested that aortic wall edema caused by sepsis could contribute to a persistent elevation in aortic characteristic impedance leading to an impaired arterial load and ventriculoarterial decoupling [33] .…”
Section: Discussionmentioning
confidence: 97%
“…This potential correlation between Ea and preload responsiveness was likely not by chance, since a recent study has explored the possibility of dynamic arterial elastance as a potential marker of cardiovascular efficiency. [32] Moreover, the previous experimental study suggested that aortic wall edema caused by sepsis could contribute to a persistent elevation in aortic characteristic impedance leading to an impaired arterial load and ventriculoarterial decoupling. [33] Whether an Ea decrease after FC indicates a better optimization of the arterial load and left ventricular workload match needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that the impact of our endotoxin infusion protocol on PPV and SVV was relatively minimal. Second, EaDyn is associated with variables related to cardiac performance that we did not evaluate in the present study (22,23), and it needs to be evaluated because the changes in continuous and pulsatile components of arterial load could increase or decrease myocardial oxygen consumption. Third, we did not evaluate the Zc and inertance of the Windkessel mode.…”
Section: Discussionmentioning
confidence: 95%
“…The main differences between our study and these previous studies are the animal models used and the method of SVV measurement. In our study, we used a swine model of endotoxin shock and measured SVV using calibrated pulse contour analysis, while the other studies used a rabbit model of endotoxin shock (22), a swine model of changes in preload, afterload, and contractility (3), and a rabbit model of changes in preload and afterload (23). In addition, the SVV in our study was measured using a different method than in previous studies, which used Doppler esophageal or conductance catheter measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation